l-cysteine prolonged fresh boar semen qualities, but not for docosahexaenoic acid - Panida Chanapiwat; Kampon Kaeoket (Czech Journal of Animal Science, 2021)
The present study aimed to develop a long-term fresh boar semen extender by adding l-cysteine and docosahexaenoic acid (DHA) into Beltsville thawing solution (BTS)-based extender. Semen samples were collected from six boars, diluted at a concentration of 3 × 109 spermatozoa/100 ml and allocated into 10 groups as follows: BTS, Merck III®, Androstar® Plus, ModenaTM, DHA 1.5 mg/ml, 3 mg/ml, and 6.25 mg/ml, l-cysteine 2.5 mM, 5.0 mM, and 10 mM. All extended semen samples were stored at 18 °C and were evaluated for progressive motility, viability, acrosome integrity, pH, and osmolality on days 0, 1, 3, 5, and 7 of storage. The results documented that on day 3, l-cysteine at 2.5 mM showed the significantly highest percentage (78.8%) of progressive motility, but not different from ModenaTM (78.8%) and Androstar® Plus (71.3%) (P < 0.05). On day 5, l-cysteine at 2.5 mM maintained progressive motility and viability up to 73.8% and 77.9%, respectively, but not different from ModenaTM (78.8% and 74.8%) and Androstar® Plus (70.0% and 76.8%) (P < 0.05). On day 7, superior progressive motility (71.3%, 77.5% and 72.5%) and viability (72.8%, 77.3% and 69.8%) were found for l-cysteine at 2.5 mM, ModenaTM and Androstar® Plus groups, respectively, when compared to the other groups (P < 0.01). However, in the present study, DHA supplementation failed to maintain fresh boar semen qualities during storage. In conclusion, adding l-cysteine at a concentration of 2.5 mM in a BTS-based extender is the optimal concentration for the preservation of fresh boar semen at 18 °C for seven days.